Epidemiology and risk of psychiatric disorders in patients with polymyositis and dermatomyositis: a nationwide population-based cohort study in Taiwan - Chin-Fang Su; Yu-Sheng Chang; Fang-Yi Wu; I-Ping Lee; Yao-Tung Lee; Jui-Hung Kao; Sheng-Hong Lin (BMJ Open)
Objectives To evaluate the incidence and risk factors for psychiatric disorders, including depression and anxiety, and assess the risk of suicide in patients with polymyositis (PM) and dermatomyositis (DM).Design Retrospective cohort study.Setting Data were obtained from Taiwan’s National Health Insurance Research Database (NHIRD) between 2000 and 2018.Participants A total of 3477 patients with PM/DM and 13 908 age- and sex-matched non-PM/DM controls were included in the study.Primary and secondary outcome measures The primary outcome was the incidence and risk of psychiatric disorders in patients with PM/DM compared with controls. Secondary outcomes included the identification of risk factors for psychiatric disorders, mortality and suicide risk in the PM/DM cohort.Results The incidence rate ratio (IRR) of psychiatric disorders was significantly higher in the PM/DM cohort than in controls (IRR 1.62, 95% CI 1.39 to 1.89), with depression being the most prevalent disorder (IRR 2.25, 95% CI 1.83 to 2.75). Key risk factors included female sex, intravenous steroid therapy, and high-dose oral steroid use. Additionally, the PM/DM cohort exhibited a higher mortality rate (IRR 3.4, 95% CI 3.15 to 3.67) and elevated suicide risk (IRR 1.99, 95% CI 0.96 to 3.86) compared with controls.Conclusion Patients with PM/DM face a significantly higher risk of psychiatric disorders, mortality and suicide. Integrating mental healthcare into the routine management of PM/DM is crucial to improving patient outcomes and reducing mortality. Future research should focus on the impact of early psychiatric interventions on survival outcomes in this population.